PENGARUH ASUPAN GIZI TERHADAP KEJADIAN OBESITAS PADA LANSIA DIWILAYAH KERJA PUSKESMAS BAITUSSALAM, ACEH BESAR - Dian Wulandari; Arnisan W. (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2022)
The population growth of the elderly above 60 years has increased rapidly. In 2015, there were 901 million people aged 60 years or over, comprising 12% of the global population. Elderly in Indonesia who are in a state of malnutrition as much as 3.4%, underweight 28.3%, ideal body weight is 42.4%, overweight is 6.7% and obesity is 3.4%. Nutritional problems in the elderly arise due to wrong eating behavior, namely an imbalance between nutritional consumption and the recommended nutritional adequacy. The research objective was to determine the effect of nutritional intake on the incidence of obesity in the elderly in the working area of the Baitussalam Community Health Center, Aceh Besar District. This research is analytic observational. The number of samples was 68 elderly (34 elderly in the obese group and 34 in the non-obese group). The research variables consisted of nutritional intake and nutritional status of the elderly. The study was conducted in January 2020, the data analysis used the chi-square test with the desired confidence level of 95%. The research data are presented in tabular and textual form. From the results of statistical tests using the chi-square test, there is no effect between nutrient intake on obesity in the elderly with the p-value on energy intake = 0.726, p-value on carbohydrate intake = 0.454, p-value on protein intake = 0.445, and p-value on fat intake = 550. In conclusion, there is no relationship between energy intake, KH intake of protein intake and fat intake on obesity in the elderly. Keywords: Energy intake, carbohydrate intake, fat intake, protein intake and elderly obesity.